Potential Students’ Grammatical Errors in Translation: A Case Study at the Fourth Semester in English Department of Letters Faculty at Universitas Pamulang - Sumartini, Tutut (TELL - US JOURNAL, 2016)
Students at English Departement, Letters Faculty, The University of Pamulang get one subject namely English-Indonesian translation at the fourth semester. In studying translation, all English knowledge and skills (Listening, Speaking, Reading dan Writing) are required to get the translation result satisfied to readers. However, there are lots of problems faced by the students which are caused by grammar and other related factors in translation. The process of translation begins with skimming in  a reading texts (Source Language=SL) until to get the main idea of the text. The students often think that careful reading is wasting of time so that they tend to try to find unfamiliar words in the dictionary straight away. This article is trying to recognize potential grammatical errors faced by a student and identify the types of errors made by the fourth semester students of the English Department,  Letters Faculty of the University of Pamulang at the periode of 2012/2013.